ANALYSIS OF THE BOOK JĀMI’ AL-AḤĀDĪTS AL-QUDSĪYAH BY ‘ISHĀM AL-DĪN AL-SHABĀBITĪ - Hanief Monady; Baharudin Zamawi (Dirosatuna: Journal of Islamic Studies, 2021)
There are many works of classical, middle, and contemporary scholars who discuss the hadith of the prophet Muhammad SAW. These works are categorized into several types, namely primary hadith books, secondary hadith books, tertiary hadith books, mixed books with other Islamic religious sciences, and so on. One of these books, is a book entitled "JÄmi' Al-Aá¸¥ÄdÄ«ts Al-QudsÄ«yah". A book that contains qudsÄ« hadiths, namely the traditions of the prophet Muhammad SAW who through the prophet as an intermediary for the words of Allah SWT. For more details, the author will discuss further in the content section of this paper. The book was written and compiled by 'IshÄm Al-DÄ«n Al-ShabÄbitÄ«. A scholar who searches for and collects qudsÄ« hadiths from many books into one book, namely "JÄmi' Al-Aá¸¥ÄdÄ«ts Al-QudsÄ«yah".